DIALOGUE BETWEEN CHURCH AND POLITICS: THE POLITICAL PARTICIPATION OF CATHOLICS (Isagoge - Journal of Humanities and Social Sciences, 2022)
The short academic essay aims to present the possible dialogue between Politics and the Catholic Church. It is true that, in many environments, it is said that the Church should not be related to political issues, since the latter are marked by evil and corruption.  However, it is the Church itself that presents the way to a good and serious political experience, rooted in faith, in moral values ​​and aiming at the common good. Furthermore, since the first Christians, there are people who stand out for their interest in good politics, which was accepted and ratified by the Magisterium of the Church, which, realizing the needs of modern times, guided the faithful to a just politics and encouraged them in the search for assist its elected representatives for the promotion of the person and the common good. However, Brazilian legislation adopts the democratic system in its current Federal Constitution, which allows greater participation of the people in the expression of their will through direct elections, as well as allowing the monitoring by the people of their legitimately elected representatives. In this way, it is understood that there is a need for greater commitment to electoral decisions, so that the legitimate will of the people and in favor of the people is fulfilled, avoiding any form of relaxation of laws or inspections for their own benefit, however, seeking to best for the common interest of society. In this sense, it is necessary that good Christians are aware of politics and give good witness to their faith, morals and good customs for the good of society.Keywords: Politics; laws; Church; common good.
Keywords: Politics; Church; Laws; Common Good